Нестационарная модель солнечной спикулы - Ладиков-Роев, Ю.П.; Логинов, А.А.; Черемных, О.К. (Проблемы управления и информатики, 2014)
Запропоновано нестаціонарну модель спікули. У рамках моделі виявлено і проаналізовано різні сценарії поведінки спікули. Відзначається, що ці сценарії якісно збігаються зі спостережуваною поведінкою спікул. Model of nonstationary spicule is proposed. In a framework of the model various scenarios of spicules behavior are revealed and analyzed. It is noted that these scenarios are in qualitative agreement with the observed behavior of the spicules.